ANALISIS KESIAPAN GURU, TANTANGAN, DAN DAMPAK PELAKSANAAN KURIKULUM MERDEKA DENGAN PENDEKATAN DEEP LEARNING DI UPTD SD INPRES OESAPA - kuli, Nadine Nelci Lidya Kuli; Maria Veridiana Wuleng; Olga Nurhayati Mesah; Maria Yunita Monga; Mathilda Efinda Saputri; Gradiana Else Abineno6; Windi Mariani Banoet; Vera Rosalina Bulu; Marfelano Bessie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teacher readiness, challenges, and the impact of implementing the Merdeka Curriculum with a Deep Learning approach at UPTD SD Inpres Oesapa. The method used is descriptive quantitative, with data collected through questionnaires and interviews involving 10 teachers and 20 students. The key findings indicate that teacher readiness is in the good category (82%), challenges faced are relatively low (46.2%), and the implementation impact is rated very high (90.2%). Students also experienced positive impacts, with improvements in independence, conceptual understanding, and learning motivation reaching 74.4%. These results indicate that the implementation of the Merdeka Curriculum with a Deep Learning approach is effective, although further mentoring in project-based learning planning and provision of supporting facilities is still needed.